2021
DOI: 10.1111/1467-9817.12356
|View full text |Cite
|
Sign up to set email alerts
|

Skill or will? The respective contribution of motivational and behavioural characteristics to secondary school students' reading comprehension

Abstract: Background: A significant number of secondary school students struggle with comprehending texts proficiently. Enhancing their reading comprehension requires knowledge about how this ability is related to various motivational and behavioural characteristics. The central aim of this study was therefore to investigate the (in)direct relationships between ninth-grade students' motivational (i.e., reading motivation and reading self-concept) and behavioural characteristics (i.e., reading strategy use, reading engag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Indeed, autonomously motivated readers read more frequently and in higher volume than their peers (De Naeghel et al, 2012;Levine et al, 2022). This high reading engagement contributes to autonomously motivated readers' comprehension skills (De Naeghel et al, 2012), whereas no connection has been found between controlled motivation and reading ability (Van Ammel et al, 2021). Indeed, reinforcing adults' autonomous motivation is essential for increasing their voluntary reading engagement (Levine et al, 2022).…”
Section: Background 21 Reading Motivationmentioning
confidence: 99%
“…Indeed, autonomously motivated readers read more frequently and in higher volume than their peers (De Naeghel et al, 2012;Levine et al, 2022). This high reading engagement contributes to autonomously motivated readers' comprehension skills (De Naeghel et al, 2012), whereas no connection has been found between controlled motivation and reading ability (Van Ammel et al, 2021). Indeed, reinforcing adults' autonomous motivation is essential for increasing their voluntary reading engagement (Levine et al, 2022).…”
Section: Background 21 Reading Motivationmentioning
confidence: 99%
“…The difference between both groups concerns which strategies are used (e.g., good comprehenders engage in more high-level processes such as monitoring their progress; Lin, 2019 ), but also when these are used (e.g., good comprehenders make more elaborations toward the text’s end). Finally, several studies examined students’ reading strategy use in relation to student characteristics such as grade, gender, achievement level, or home language (e.g., Denton et al, 2015 ; Van Ammel et al, 2021 ). For example, the study of Denton et al (2015) on secondary students reported higher strategy use for girls, older students, and high comprehenders.…”
Section: Reading Comprehension Strategy Usementioning
confidence: 99%
“…Skilled readers use metacognitive strategies to identify when they are not understanding some part of the text and, consequently, mobilize appropriate cognitive strategies to overcome this difficulty (Graesser, 2007 ; Pereira-Laird & Deane, 1997 ; Perfetti et al, 2005 ). In fact, the knowledge and use of reading strategies have been identified as significant predictors of reading comprehension (Frid & Friesen, 2020 ; Law, 2009 ; Liao et al, 2021 ; Muijselaar & de Jong, 2015 ; Roeschl-Heils et al, 2003 ; Samuelstuen & Bråten, 2005 ; Van Ammel & Keer, 2021 ; Van Kraayenoord et al, 2012 ). However, contrary to reading and linguistic skills, the existence of reciprocal relations between metacognitive skills and reading comprehension has been scarcely explored.…”
Section: Interrelationships Between Reading Comprehension and Metacog...mentioning
confidence: 99%
“…For this reason, and given that this is a 3-year longitudinal study starting in grade 4, we address oral reading fluency instead of word recognition. Additionally, the CFR does not include other components of interest, such as reading strategy use, which is closely interrelated with reading comprehension across a wide range of grade levels (Frid & Friesen, 2020 ; Law, 2009 ; Liao et al, 2021 ; Muijselaar & de Jong, 2015 ; Roeschl-Heils et al, 2003 ; Samuelstuen & Bråten, 2005 ; Van Ammel & Keer, 2021 ; Van Kraayenoord et al, 2012 ).…”
mentioning
confidence: 99%